Analisis Hukum Perlindungan Konsumen terhadap Praktik Pengoplosan Bahan Bakar Minyak Pertamax Berdasarkan Undang-Undang Nomor 8 Tahun 1999 (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The practice of adulterating RON 92 (Pertamax) fuel has the potential to violate consumer rights and is contrary to applicable laws and regulations. The practice of mixing lower-quality fuel and then marketing it as RON 92 results in material and immaterial losses for users, including reduced vehicle performance and a loss of trust in business operators. This research aims to analyze the legal protections available to consumers regarding the practice of adulterating fuel based on Law Number 8 of 1999 concerning Consumer Protection and related provisions in Law Number 22 of 2001 concerning Oil and Gas. The research method used is normative legal research with a library research approach, through analysis of relevant laws and regulations, scientific literature, and secondary legal sources. The results indicate that the practice of adulterating fuel violates consumers' rights to comfort, security, safety, and accurate information as stipulated in Article 4 of the Consumer Protection Law, and violates the obligations of business actors as stipulated in Articles 7 and 8 of the Consumer Protection Law. Business actors can be held accountable for civil damages, dispute resolution through the Consumer Dispute Resolution Agency (BPSK), or subject to administrative and criminal sanctions in accordance with the Oil and Gas Law. Therefore, legal protection for consumers in cases of fuel adulteration requires an interconnectedness between effective government oversight, firm law enforcement, business actor accountability, and increased consumer legal awareness to ensure legal certainty and fairness in trade activities.